School Physical Education in the development of psychomotricity (Research, Society and Development, 2021)
Physical Education appears with great responsibility at school, structuring the appropriate environment for children to experience and feel their relationship with the environment. Within the presented scenario, the psychomotor activities that lead the child to become aware of his body, must be practiced since the beginning of childhood. The objective was to verify the effects of psychomotricity in Physical Education and practice of physical exercises for the integral development of the child. This work was carried out by means of an exploratory reading of bibliographic materials, based on the analysis of books, magazines, website articles (scielo and google academic) that address the importance of psychomotricity as a tool in Physical Education. The results evidenced were that psychomotricity develops motor skills when worked in physical education classes, and collaborates for affective, cognitive and motor development. This process occurs gradually over the child's growth and maturation. In this way, psychomotricity works by providing subsidies for the child's adaptation to his basic needs. And so, when worked in the school context, it stimulates the harmonious and integral development of the being. When verifying research and studies around children with and without motor difficulties, it can be concluded that motor intervention causes considerable progress in motor, cognitive and affective development, and that these in turn, collaborate with other areas of learning (reading and writing for example) and with the child's full development. Psychomotor activities should be used as an apparatus of physical education in early childhood education, since there is a consensus in the literature that such activities help children in their global development.